A 1-year follow-up study on immunological changes following deep brain stimulation in patients with epilepsy - Pabitra Basnyat (Nature Portfolio, 2021)
Abstract The aim of this study was to evaluate the effects of deep brain stimulation of the anterior nucleus of the thalamus (ANT-DBS) on systemic inflammatory responses in patients with drug-resistant epilepsy (DRE). Twenty-two Finnish patients with ANT-DBS implantation were enrolled in this pilot study. Changes in plasma interleukin-6 (IL-6) and interleukin-10 (IL-10) levels were examined using generalized estimating equation models at seven time points (before DBS surgery and 1, 2, 3, 6, 9 and 12 months after implantation). In the whole group, the IL-6/IL-10 ratio decreased significantly over time following ANT-DBS, while the decrease in IL-6 levels and increase in IL-10 levels were not significant. In the responder and nonresponder groups, IL-6 levels remained unchanged during the follow-up. Responders had significantly lower pre-DBS IL-10 levels before the ANT-DBS treatment than nonresponders, but the levels significantly increased over time after the treatment. In addition, responders had a higher pre-DBS IL-6/IL-10 ratio than nonresponders, and the ratio decreased for both groups after treatment, but the decrease did not reach the level of statistical significance. The rate of decrease in the ratio per month tended to be higher in responders than in nonresponders. These results may highlight the anti-inflammatory properties of ANT-DBS treatment associated with its therapeutic effectiveness in patients with DRE. Additional studies are essential to evaluate the potential of the proinflammatory cytokine IL-6, the anti-inflammatory cytokine IL-10, and their ratio as biomarkers to evaluate the therapeutic response to DBS treatment, which could facilitate treatment optimization.